Training structure of powerlifters with regard to biological rhythms and operational functional condition - T.N. Shutova; T.P. Vysotskaya (Physical Education of Students, 2018)
Purpose: to develop and experimentally confirm the structure of training cycles, training load and sports results with regard to the biological rhythms and functional condition of powerlifters. Material: the study involved qualified powerlifters (n = 40). The diagnostic procedure was performed on the Omega hardware complex. Ostberg questionnaire was applied to determine the athlete’s chronotype. According to the results of the questionnaire, athletes were divided into morning, evening and mixed chronotypes. In the experimental group (N1, n = 20), intensive training was conducted at the peak of the biological rhythm. Medium and low-intensity training was performed in the phase of reducing the biorhythms activity. Standard training was performed in the control group (N2, n = 20), without regard to chronotypes. Results: it was determined that the application of non-standard means of athletes training at the peak of the biological rhythms activity and in the rising phase of the biogram significantly influences on the increase in maximum strength results. Non-standard means include Crossfit training and a reverse pyramid (the maximum weight is applied at the beginning of the training, in the subsequent approaches the weight reduces, the number of repetitions increases). It is determined the significant differences between groups in the control exercises: hanging pull-up/chin up, parallel bar dips, hanging on the crossbar. Conclusions: the training of qualified powerlifters should be based on their chronotype. The main mean of the training process optimizing of athletes should be a biogram, reflecting the physical, emotional and intellectual biological rhythm.